POTENSI PEMBIAYAAN MUDHARABAH AGRIBISNIS TERHADAP KESEJAHTERAAN MASYARAKAT: EFEK MODERASI ECO LITERACY DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Normasyhuri, Khavid; Huda, Ahsanal (ITB AAS Indonesia Surakarta, 2025)
The main problem identified is the inequality of access to mudharabah financing in the agricultural sector, which hinders farmer empowerment. In addition, the lack of understanding of eco-literacy in the community affects the sustainable management of natural resources. This study aims to examine the effect of agribusiness mudharabah financing on community welfare, by considering the role of eco-literacy as a moderating variable in supporting the achievement of SDGs. A quantitative approach was used with SmartPLS 4.0 software for data analysis. Primary data were collected through purposive sampling and measured using a Likert scale with a total of 400 respondents. The research findings show that mudharabah financing has a positive impact on community welfare, and eco-literacy strengthens this relationship. Farmers who understand sustainability are more likely to manage their businesses more efficiently and environmentally friendly, which has an impact on the achievement of SDGs such as No Poverty, No Hunger, Reduced Inequality, and Gender Equality. This study contributes to understanding how sharia financing and eco-literacy can contribute to sustainable development. These findings provide a basis for the development of more inclusive and sustainable financing products and practical recommendations for policy makers to strengthen ecological literacy among farmers.